Role of the intermittent physical exercise on the flow-mediated vasodilation in elite volleyball players - Ammendolia, A.; Care, I.; Ferragina, A.; Miceli, S.; Iamundo, M.; Iona, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In literature there are a lot of studies that report the importance of the physical exercise to improve cardiovascular functions (1). Recently, the development of new technologies made possible the not invasive study of vascular functional parameters like the flow mediated vasodilation, valuable only since few years (2). The aim of this study was to evaluate the changes of the flow mediated vasodilatation and of the diameter of the brachial artery, after a programmed training, in a group of young elite volleyball players. Methods We enrolled 8 young elite athletes (men, average age 20+6). After informed consent, we have undergone them to the complete cardiovascular evaluation with echocardiographic measurement of the diameter, of the brachial artery of both upper limbs, in diastole before the beginning of the pre-championship training and at the middle of the championship. The measurement of the flow mediated vasodilatation has been performed by the digital pulse volume amplitude (PVA) during reactive hyperemia. The statistical analysis was conducted using t-test, considering significant P<0.05. Results: At the middle of the championship we observed a not significant reduction of the cardiac frequency (59+13/min vs 54+7/min; p=0.102), a significant increase of the systolic blood pressure values (111+6 mmHg vs 121+7 mmHg; p=0.045), a significant increase of the diameter of the brachial artery in the right limb (0.31+0.04 cm vs 0.37+0.04 cm; p=0.016) and in the left limb (0.30+0.03 cm vs 0.38+0.07 cm; p=0.019) and a significant increase of flow-mediated vasodilation (1.7+0.2 vs 2.3+0.8 cm; p=0.038). No significant changes of the diastolic blood pressure were observed. Discussion: Previous studies have demonstrated a higher flow-mediated vasodilation levels in athletes after aerobic exercise (3-4). Our data, for the first time, demonstrate that also the habitual intermittent physical exercise increases the flow-mediated vasodilation and the diameter of the brachial artery, improving the vascular adaptation.